La médicalisation des problématiques suicidaires : l’exemple d’un service d’urgence psychiatrique - Michela Canevascini (Criminocorpus)
This article analyzes the care given to individuals with suicidal thoughts and behavior in the setting of a psychiatric emergency services unit. When confronted with suicide related issues, caregivers rely on tools that are meant to objectify psychiatric practice, such as the evaluation of potential suicidality and the establishment of a psychiatric diagnosis. However, caregivers are confronted with numerous patients who present mild psychological distress, which puts into question the pertinence of a medical apparatus in this context. Although caregivers appear to be critical of the risks of medicalization, institutional constraints, health insurance, as well as disciplinary rationales play an important role in medicalization of suicidality.